The digital technological evolution for women’s health: lights and shadows in medicine (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Femtech defines a business system in which digital technologies are studied and used to support women in monitoring their health problems. Despite the advantages of digital medicine and the economic-cultural push in terms of innovation in the health system, these technologies are not yet inclusive, accessible and usable equally by all women. They also present countless critical issues in terms of scientific-methodological rigor and appropriateness of medical practice in its many facets. The article aims to contextualize Femtech in the current healthcare landscape, to present its main products and to focus on its advantages and criticalities, to promote correct digital literacy.
Keywords: Woman’s health; gender gap; Femtech; digital healthcare; digital literacy; alfabetizzazione digitale